Compact low‐profile body worn and wrist worn lightweight antenna for ISM and GPS band navigation and medical applications. Issue 9 (11th August 2018) - Das, Saumya; Islam, Hashinur; Bose, Tanushree
Abstract: This article investigates the performance of a compact dual band flexible antenna for wrist wearable applications of ISM and GPS frequencies. A semi rigid, lightweight material "Arlon foam clad 100" is chosen as a substrate for designing this wearable antenna. Analysis results from past journal papers are taken in verifying permittivity of the substrate material. Simulation tool is used to measure significant antenna parameters under three different cases named as flat wearable, cylindrical wearable, and wrist wearable for accepting the proposed conformal radiator in the application of navigation, animal tracking, health monitoring, and so on. Moreover, a prototype of this wearable antenna is developed and tested under all three above mentioned cases to confirm the simulated results.